The Living Wage campaign in the UK. Issue 6 (2nd October 2017) - Heery, Edmund; Hann, Deborah; Nash, David
Abstract : Purpose: This paper presents an account of the UK campaign for the voluntary Living Wage, an example of civil regulation. The purpose of this paper is to identify and characterize the actors involved in the campaign, describe methods used and examine direct and indirect consequences of the campaign. Design/methodology/approach: A mixed-method design is employed, reflecting the broadly framed purpose of the research. The research used semi-structured interviews with campaigners, union representatives and employers, observation of campaign activities and the creation of a database of Living Wage employers. Findings: The campaign originated in the community organizing movement, but has involved a broad range of labor market actors, both "new" and "old." A continuum of campaigning methods has been used, stretching from community mobilization to appeals to employer self-interest and corporate social responsibility. The campaign has recruited 3, 000 employers, led to wage increases for thousands of workers and registered indirect effects by shaping the policies of governments, employers and unions. Originality/value: The research presents a novel account of the UK's distinctive Living Wage campaign, a notable example of the civil regulation of the labor market.